The impact of start strategy on start performance in alpine skiing exists on flat, but not on steep inclines - Supej, M.; Nedergaard, N. J.; Nord, J.; Holmberg, H. C. (Journal of Sports Sciences, 2019)
Here, we explored the relationship between incline and start strategy during alpine skiing. Eight FIS skiers performed starts on a flat (3°) and steep (21°) incline employing five different strategies. Their times, trajectories and velocities were monitored with a GNSS system and video. A significant interaction was observed between slope incline and start strategy with respect to the skier`s exit velocity (p < 0.001, eta2p = 0.716), but not for the start section time (p = 0.732, eta2p = 0.037). On the almost flat incline, both section time (p = 0.022, eta2p = 0.438) and exit velocity (p < 0.001, eta2p = 0.786) were influenced significantly by start strategy, with four V2 skate-pushes being optimal. On the steep incline, neither section time nor exit velocity was affected significantly by start strategy, the fastest section time and exit velocity being attained with four and two V2 skate-pushes, respectively. In conclusion, these findings demonstrate that the start strategy exerts considerable impact on start performance on almost flat inclines, with strategies involving three or more V2 skate-pushes being optimal. In contrast, start performance on the steep incline was not influenced by strategy.